A Reconstructed Cu2P2O7 Catalyst for Selective CO2 Electroreduction to Multicarbon Products. (10th December 2021) - Sang, Jiaqi; Wei, Pengfei; Liu, Tianfu; Lv, Houfu; Ni, Xingming; Gao, Dunfeng; Zhang, Jiangwei; Li, Hefei; Zang, Yipeng; Yang, Fan; Liu, Zhi; Wang, Guoxiong; et al.
Abstract: The electrochemical CO2 reduction reaction (CO2 RR) over Cu‐based catalysts shows great potential for converting CO2 into multicarbon (C2+ ) fuels and chemicals. Herein, we introduce an A2 M2 O7 structure into a Cu‐based catalyst through a solid‐state reaction synthesis method. The Cu2 P2 O7 catalyst is electrochemically reduced to metallic Cu with a significant structure evolution from grain aggregates to highly porous structure under CO2 RR conditions. The reconstructed Cu2 P2 O7 catalyst achieves a Faradaic efficiency of 73.6 % for C2+ products at an applied current density of 350 mA cm −2, remarkably higher than the CuO counterparts. The reconstructed Cu2 P2 O7 catalyst has a high electrochemically active surface area, abundant defects, and low‐coordinated sites. In situ Raman spectroscopy and density functional theory calculations reveal that CO adsorption with bridge and atop configurations is largely improved on Cu with defects and low‐coordinated sites, which decreased the energy barrier of the C−C coupling reaction for C2+ products. Abstract : The electrochemical in situ reconstruction of Cu2 P2 O7 during CO2 electroreduction generates highly porous Cu with abundant defects and low‐coordinated sites, which facilitate CO adsorption with bridge and atop configurations, thus resulting in a high‐rate production of C2+ fuels and chemicals.